Analysis of Factors Causing Delays in Ballast Pump Repair Using the Kaiser-Meyer-Olkin and RCA Methods at KM XXX at PT XYZ - Febian Rizky Purnama; Mega Cattleya PA Islami (Jurnal Serambi Engineering, 2026)
The shipping sector is a crucial element in a nation's shipping operations, particularly in ensuring the optimal performance of essential components such as ballast pumps. However, the repair time for the ballast pumps on the KM XXX ship at the PT XYZ shipyard often exceeds the initial estimate (seven working days), resulting in financial losses and increased waiting time for the ship at port. This study is designed to identify the main determinants behind the delays in ballast pump repairs and formulate strategic recommendations to optimize maintenance effectiveness. The analytical methods applied include Kaiser-Meyer-Olkin (KMO) for factor analysis and Root Cause Analysis (RCA) supplemented by a Fishbone Diagram to determine the root cause of a problem. By determining the main factors and root causes, this study presents detailed and systematic improvement recommendations. These recommendations are designed to optimize the effectiveness of ballast pump maintenance and mitigate adverse consequences on ship operational performance.